Central African Republic : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the financial system stability assessment (FSSA) on the Central African Republic. The assessment reveals that the liquidity position of the financial sector has improved in recent years. This reflects a more favorable economic environment following the end of hostilities, higher remittance receipts, increased donor financing, and a weak loan demand. The assessment also reveals that although systemic risks presently appear manageable, the banking system exhibits important weaknesses. Significant structural impediments weigh on the capacity of the financial sector to support development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet